All-optical modulation in Black Phosphorus functionalized microfibre coil resonator. (21st October 2020) - Yin, Yu; Li, Shi; Ren, Jing; Du, Yanqiu; Farrell, Gerald; Brambilla, Gilberto; Wang, Pengfei
Abstract: All-optical modulation is experimentally demonstrated in a microfibre coil resonator (MCR) functionalized with black phosphorus (BP) nanosheets (BP-MCR). The BP nanosheets is deposited onto microfibre and then microfibre is wrapped on a PMMA rod covered with UV-curable low refractive index polycarbonate (PC) resin. The BP-MCR modulation properties are regulated based on BP absorption, photo-thermal and optical Kerr effects. The resonance wavelength and extinction ratio responsivity to incident pump power can attain ∼0.033 nm mW −1 and ∼0.180 dBm mW −1, while the averaged rising/falling response time is ∼9.58/8.53 ms. The device could find applications as all-optical modulator, optical switch or tunable optical filter.